A 4000-species dataset provides new insight into the evolution of ferns - Testo, Weston; Sundue, Michael (Molecular phylogenetics and evolution, 2016)
[Display omitted] •Ferns and the seed plant clade diverged by the late Silurian.•Most fern lineages are older than previously reported.•Leptosporangiate fern families arose well before their radiation in the Cenozoic.•Epiphytic growth is not associated with increased diversification. Ferns are the second-most diverse lineage of vascular plants on Earth, yet the best-sampled time-calibrated phylogeny of the group to date includes fewer than 5% of global diversity and was published seven years ago. We present a time-calibrated phylogeny that includes nearly half of extant fern diversity. Our results are evaluated in the context of previous studies and the fossil record, and we develop new hypotheses about the radiation of leptosporangiate ferns. We used sequence data from six chloroplast regions for nearly 4000 species of ferns to generate the most comprehensive phylogeny of the group ever published. We calibrate the phylogeny with twenty-six fossils and use an array of phylogenetic methods to resolve phylogenetic relationships, estimate divergence times, and infer speciation, extinction, and net diversification rates. We infer a mid-late Silurian origin for ferns (including horsetails) and an early Carboniferous origin for leptosporangiate ferns. Most derived fern families appeared in the Cretaceous and persisted for millions of years before rapidly diversifying in the Cenozoic. We find no evidence of differential rates of diversification among terrestrial and epiphytic species. Our findings challenge previous hypotheses on the evolutionary history of ferns and present a new paradigm for their Cenozoic radiation. We estimate earlier divergences for most fern lineages than were reported in previous studies and provide evidence of extended persistence of major fern lineages prior to rapid diversification in the last fifty million years.